BATTLE ON THE LOMBA, 1987 THE DAY A SOUTH AFRICAN ARMOURED BATTALION SHATTRED ANGOLA’S LAST MECHANISED OFFENSIVE: A CREW COMMANDER’S ACCOUNT - Mannall, David (Scientia Militaria - South African Journal of Military Studies, 2015)
Writing about the Namibian Border War and South African involvement in the Angolan Civil War is difficult. Many South Africans have been conscripted or willingly served in the military at the time and find it difficult to distance themselves from their own experiences and their personal involvement in many of the operations that were conducted by the South African military. The issue is also clouded by the current South African government’s association with what happened on the other side of the hill[i]and, more specifically, their support for the winning narrative of the Cuban–Angolan forces. Many previous South African Defence Force (SADF) soldiers are also facing the wounds of post-traumatic stress because of their exposure to the battlefield experiences of the war. It is very often difficult to navigate between perceptions and reality and to find the truth in the debate about who won the so-called Battle for Cuito Cuanavale.